Comparison of physical and mechanical properties of mineral trioxide aggregate and Biodentine - Naziya Butt; Sangeeta Talwar; Sarika Chaudhry; Ruchika Roongta Nawal; Seema Yadav; Anuradha Bali (Wolters Kluwer Medknow Publications, 2014)
Background: Mineral trioxide aggregate (MTA) fulfills many of the ideal properties of the root-end filling material. However, its low cohesive property often makes it difficult to handle. Biodentine, new calcium-silicate-based cement has been developed to improve some MTA drawbacks such as its difficult handling property and long-setting time. Aim: The objective of this study was to compare at different times the microleakage of roots filled with Biodentine and white MTA (WMTA)-Angelus and to investigate their setting time, handling properties and compressive strength. Materials and Methods: Root canals of single-rooted teeth were instrumented, filled with either Biodentine or WMTA-Angelus (n = 15 each) with two positive and two negative control roots and stored at 37°C. Sealing was assessed at 4, 24 h, 1, 2, 4, 8, and 12 weeks by a fluid filtration method. The initial setting time, handling properties, and compressive strength of the test groups were investigated by a vicat needle, questionnaire of operational hand feel, and universal instron machine, respectively. Results: Significant differences in microleakage were found between two groups at 4-h and 24 h (P < 0.05) and no difference at 1, 2, 4, 8, and 12 weeks. No significant difference was seen in the setting time of MTA-Angelus and Biodentine, though latter was found to have better handling consistency. Compressive strength of Biodentine was significantly higher than MTA-Angelus. Conclusions: The results suggest that the new calcium-silicate-based endodontic cement provides improvement in sealing ability as well as clinical manageability of dental filling materials.